Number and Locations of Agonist Binding Sites Required to Activate Homomeric Cys-Loop Receptors - Rayes, Diego Hernán (2009)
Homo-pentameric Cys-loop receptors contain five identical agonist binding sites, each formed at a subunit interface. To determine the number and locations of binding sites required to generate a stable active state, we constructed a receptor subunit with a mutation that disables the agonist binding site and a reporter mutation that alters unitary conductance and coexpressed mutant and nonmutant subunits. Although receptors with a range of different subunit compositions are produced, patch-clamp recordings reveal that the amplitude of each single-channel opening event reports the number and, for certain subunit combinations, the locations of subunits with intact binding sites. We find that receptors with three binding sites at nonconsecutive subunit interfaces exhibit maximal mean channel open time, receptors with binding sites at three consecutive or two nonconsecutive interfaces exhibit intermediate open time, and receptors with binding sites at two consecutive or one interface exhibit brief open time. Macroscopic recordings after rapid application of agonist reveal that channel activation slows and the extent of desensitization decreases as the number of binding sites per receptor decreases. The overall results provide a framework for defining mechanisms of activation and drug modulation for homo-pentameric Cys-loop receptors.